2013
DOI: 10.1002/cm.21113
|View full text |Cite
|
Sign up to set email alerts
|

The multiplicity of human formins: Expression patterns in cells and tissues

Abstract: Formins are actin binding proteins conserved across species from plants to humans. The formin family is defined by their common FH2 domains. The 15 distinct human formins are involved in a broad range of cellular functions, including cell adhesion, cytokinesis, cell polarity, and cell morphogenesis. Their commonality is actin polymerization activity inherent to FH2 domains. While still requiring much study, biochemical activity of formins has been carefully described. In contrast, much less is known of their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 41 publications
1
53
1
1
Order By: Relevance
“…Arp2/3 forms the branched network in lamellipodia and is thought to be linked to nascent FAs through interaction with FAK (19)(20)(21) or vinculin (22). The formin family of actin nucleators, which generates linear actin bundles (23), is more diverse, although formins share a common actin assembly core domain (24), (25). Recent work has begun to ascribe the generation of particular actin structures to some of the 15 formins in mammalian cells, particularly members of the diaphanous family and FHOD1 (26)(27)(28)(29).…”
Section: Significancementioning
confidence: 99%
“…Arp2/3 forms the branched network in lamellipodia and is thought to be linked to nascent FAs through interaction with FAK (19)(20)(21) or vinculin (22). The formin family of actin nucleators, which generates linear actin bundles (23), is more diverse, although formins share a common actin assembly core domain (24), (25). Recent work has begun to ascribe the generation of particular actin structures to some of the 15 formins in mammalian cells, particularly members of the diaphanous family and FHOD1 (26)(27)(28)(29).…”
Section: Significancementioning
confidence: 99%
“…Complete blood counts were surprisingly normal, indicating that FMNL1 is unlikely to serve a critical role in hematopoiesis. In addition to FMNL1, we have previously reported that other formins, such as Dia1 and FHOD1, are expressed in macrophages (Krainer et al, 2013), yet we observed no compensatory changes in the expression of other formins when FMNL1 was depleted from macrophages here. Strikingly, the tissue distribution of residential macrophages from knockout mice was significantly reduced compared to in WT, most notably in the liver.…”
Section: Discussioncontrasting
confidence: 47%
“…2E); IMM-02 showed an equivocal effect. The difference in induction of stabilization between treated and untreated NIH 3T3 and SW480 cells is unclear; it may reflect fundamental differences in dynamic instability of transformed and nontransformed cells (31,33), or alternatively, the nature of the affected target formin expressed in these two different cell types (34).…”
Section: Resultsmentioning
confidence: 99%